The pore structure and gating mechanism of K2P channels. - Piechotta, P; Rapedius, M; Stansfeld, P; Bollepalli, M; Ehrlich, G; Erhlich, G; Andres-Enguix, I; Fritzenschaft, H; Decher, N; Sansom, MS; Tucker, S; Baukrowitz, T (2011)
Two-pore domain (K2P) potassium channels are important regulators of cellular electrical excitability. However, the structure of these channels and their gating mechanism, in particular the role of the bundle-crossing gate, are not well understood. Here, we report that quaternary ammonium (QA) ions bind with high-affinity deep within the pore of TREK-1 and have free access to their binding site before channel activation by intracellular pH or pressure. This demonstrates that, unlike most other K(+) channels, the bundle-crossing gate in this K2P channel is constitutively open. Furthermore, we used QA ions to probe the pore structure of TREK-1 by systematic scanning mutagenesis and comparison of these results with different possible structural models. This revealed that the TREK-1 pore most closely resembles the open-state structure of KvAP. We also found that mutations close to the selectivity filter and the nature of the permeant ion profoundly influence TREK-1 channel gating. These results demonstrate that the primary activation mechanisms in TREK-1 reside close to, or within the selectivity filter and do not involve gating at the cytoplasmic bundle crossing.